A SEMIOTIC ANALYSIS IN MUSIC VIDEO OF BLANK SPACE BY TAYLOR SWIFT - Oktavyanthi, Indriani; Kholiq, Muh (Universitas Gunadarma, 2018)
Music video has a signs and different meaning. This research aims to know the signs used and to find out denotation and connotation meaning in the music video of Blank Space by Taylor Swift. The method used in analysis this music video is qualitative. The results obtained from this research are the semiotic signs found namely visual signs, verbal signs in song lyrics, denotation and connotation meaning.